2014
DOI: 10.1088/2040-8978/16/10/105404
|View full text |Cite
|
Sign up to set email alerts
|

Entropic uncertainty minimum for angle and angular momentum

Abstract: Uncertainty relations are key components in the understanding of the nature of quantum mechanics. In particular, entropic relations are preferred in the study of angular position and angular momentum states. We propose a new form of angle–angular momentum state that provides, for all practical purposes, a lower bound on the entropic uncertainty relation, , for any given angular uncertainty, thus improving upon previous bounds. We establish this by comparing this sum with the absolute minimum value determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In the course of the present work we have found that less general expressions than equations ( 9) and ( 14) have been discussed in the literature in the context of a minimum entropic angular position and angular momentum quantum states [40].…”
mentioning
confidence: 92%
“…In the course of the present work we have found that less general expressions than equations ( 9) and ( 14) have been discussed in the literature in the context of a minimum entropic angular position and angular momentum quantum states [40].…”
mentioning
confidence: 92%